Pelatihan Google Classroom Untuk Meningkatkan Kompetensi Guru SD Dalam Pembelajaran Daring - Nureyzwan Sabani; Reza Ulva Tamimi; Lisnawati Ruhaena (Lentera Dua Indonesia, 2022)
Teacher are not ready to carry out online learning in using online media during the covid-19 pandemic because of the lack competence of teachers. The purpose of this activity is to improve the competence of elementary school teachers in using Google Classroom to support online learning. The Program of Community Service is carried out by holding google classroom training for elementary school teachers through the Zoom aplication. To find out the increase in teacher competence, a pretest and posttest were carried out, followed by a t-test. The test results show that there is a significant difference between the results of the pretest and posttest with Z score of -2.032 and a p value of 0.042 <0.05, so it can be concluded that there is an increase in the competence of elementary school teachers in using google classroom after being given training. With this training, it is hoped that teachers can carry out learning with the help of Google Classroom so that online learning can be managed and implemented properly.